Karakteristik Naskah Terjemahan Al-Qur’an Pegon Koleksi Perpustakaan Masjid Agung Surakarta - Gusmian, Islah (Lajnah Pentashihan Mushaf Al-Qur'an, 2012)
This article describes the characteristics ofÃ‚Â aÃ‚Â manuscriptÃ‚Â containingÃ‚Â a trans-lation of the QurÃ¢â‚¬â„¢an intoÃ‚Â Javanese PegonÃ‚Â script found in theÃ‚Â collection of the library of the Great Mosque of Surakarta. The translation were composed as teaching material for use in the Madrasah Manba'ul-Ulum, an Islamic boarding school established withÃ‚Â theÃ‚Â support of the Surakarta Kraton and under the authority of His Majesty Sri Pakubuwono IX (1861-1893). The level of language used in the Pegon text isÃ‚Â ordinaryÃ‚Â Javanese withÃ‚Â the modelÃ‚Â for theÃ‚Â translation being based on exegesis which is the critical explanaton or interpretation ofÃ‚Â a religiousÃ‚Â text. The manuscript is historical proof of the intimate relationship existing between Islam and the Kraton, as well as theÃ‚Â palaceÃ¢â‚¬â„¢s role in the development of Islamic education,Ã‚Â in Surakarta in the late of 19th century CE. The manuscript contributed to enrichingÃ‚Â pesantren learningÃ‚Â whichÃ‚Â is more widelyÃ‚Â known for its traditions ofÃ‚Â scientific Islamic jurisprudenceÃ‚Â (fiqh)Ã‚Â and Sufism at that time.